The Impact of Curriculum Change and Parental Support on The Effectiveness of Inclusive Education in Indonesian Primary Schools - Penti Yulyanti; Edi Harapan; Heri Setiyo Nugroho (Journal of Social Work and Science Education, 2026)
Although inclusive education has been widely promoted to ensure equal access for students with special needs, empirical studies examining the combined role of curriculum adaptation and parental support at the primary school level remain limited, particularly in rural contexts. This study aims to analyze the influence of curriculum changes and parental support on the effectiveness of inclusive education in primary schools in Sirah Pulau Padang Subdistrict. A quantitative survey design was employed involving teachers, principals, and parents. Data were collected using validated and reliable instruments and analyzed through multiple regression analysis. The findings demonstrate that curriculum changes significantly influence the effectiveness of inclusive education, parental support also has a significant effect, and both variables simultaneously contribute positively and significantly to inclusive education outcomes. The novelty of this study lies in integrating institutional (curriculum adaptation) and familial (parental support) factors within a single empirical model in a rural primary education setting. These findings provide practical implications for policymakers and school leaders in strengthening adaptive curriculum implementation and fostering collaborative partnerships with parents to enhance inclusive education effectiveness.